2009
DOI: 10.1016/j.photonics.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon resonance and electric field amplification of crossed gold nanorods

Abstract: Here we explore the unusual plasmon resonances of crossed gold nanorod structures of varying geometries. Using numerical simulations, we show that the resonances of simple rods are hybridized and blue-shifted in the composite structures and that these structures are surrounded by spatially extended and high intensity electric fields. This attribute suggests several potential uses for these shapes, for example as a nano-antenna for the generation of two-photon fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Such a phenomenon resulting in the collective excitations of the electrons at the interface between a conductor and an insulator is described by evanescent electromagnetic waves that are not necessary located at the interface. , Spherical NPs as well as anisotropic ones are presently determining materials in several fields. Moreover, the anisotropy in shape of the NPs offers further properties whose the applications are extended over chemistry and physics areas. , Among various 3-D metallic nanostructures, gold nanorods (GNRs) have received considerable attention due to their remarkable properties based on the so-called surface plasmon resonance excitation. , These unusual properties have many applications in a wide multidisciplinary field from electronics to medicine. , Recently, by a modeling approach, Nørskov et al showed that small gold nanoparticles can exhibit unusual catalytic activity toward the carbon monoxide oxidation. Moreover, Cui et al emphasized the importance of the catalyst morphology in its activity improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Such a phenomenon resulting in the collective excitations of the electrons at the interface between a conductor and an insulator is described by evanescent electromagnetic waves that are not necessary located at the interface. , Spherical NPs as well as anisotropic ones are presently determining materials in several fields. Moreover, the anisotropy in shape of the NPs offers further properties whose the applications are extended over chemistry and physics areas. , Among various 3-D metallic nanostructures, gold nanorods (GNRs) have received considerable attention due to their remarkable properties based on the so-called surface plasmon resonance excitation. , These unusual properties have many applications in a wide multidisciplinary field from electronics to medicine. , Recently, by a modeling approach, Nørskov et al showed that small gold nanoparticles can exhibit unusual catalytic activity toward the carbon monoxide oxidation. Moreover, Cui et al emphasized the importance of the catalyst morphology in its activity improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared with the EF of the crossed Ag chains with 30° model (Figure a, EF = 1.8 × 10 3 ), the EF of crossed Ag chains with 90° model (Figure c, EF = 7.2 × 10 5 ) could be increased by the magnitude’s 2–3 orders. Cortie et al have simulated the resonance behavior crossed gold nanorod structures with different angles using the discrete dipole approximation. They have thought that the SPR to red-shift was caused by increasing the angle that is between the arms of the gold nanorod structures.…”
Section: Resultsmentioning
confidence: 99%
“…We also study the hybridization of plasmon modes when two crosses are brought in close proximity (30 nm) of one another along one of their arms. The plasmonic property of metallic nanocross has been reported before in a few studies. Varellen and co-workers , have done extensive study on the effect of size and angle between the two arms of a cross on the observed plasmonic spectrum. They have also demonstrated the application of a nanocross coupled to a nanorod for LSPR sensing .…”
Section: Introductionmentioning
confidence: 84%